2006
DOI: 10.1179/174329406x126771
|View full text |Cite
|
Sign up to set email alerts
|

Glow discharge modified tissue culture polystyrene: Role of surface chemistry in cellular attachment and proliferation

Abstract: A radio frequency glow discharge has been used to selectively deposit non-polar hydrocarbon films onto tissue culture grade polystyrene surfaces. The resulting surfaces have been studied using X-ray photoelectron spectroscopy, contact angle analysis and atomic force microscopy. Regions with differing surface chemistry and polarity have been produced on the same substrate using a simple masking technique and allowed the spatially controlled attachment of mammalian cells. The attachment of cells to plasma modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The signals at 6.4-7.2 ppm (Spec. b) could be assigned to the protons of benzene rings in polystyrene [12,13]. Moreover the peak area of Spec.…”
Section: Resultsmentioning
confidence: 98%
“…The signals at 6.4-7.2 ppm (Spec. b) could be assigned to the protons of benzene rings in polystyrene [12,13]. Moreover the peak area of Spec.…”
Section: Resultsmentioning
confidence: 98%
“…Another explanation could be the presence of C = O functional groups in the plasma polymer. It has been shown that the surface concentration of carbonyl groups influences the cellular adhesion of Chinese ovary hamster [23] and bovine aortic [24] cell lines. As this functional group was only observed on the Ar/C 2 H 2 plasmatreated sample (Fig.…”
Section: Cells and Plasma Polymer Interactionsmentioning
confidence: 99%